Inflation Volatility and COVID-19 In Indonesian: ARIMA Method - Nugroho Suryo Bintoro; Kartika Sari (AIBPM Publisher, 2022)
Inflation is one of the most widely tested economic variables both theoretically and empirically. Stable inflation is a sign that sustainable economic growth provides benefits for improving people's welfare. This study aims to analyze the impact of Covid-19 on volatility inflation in Indonesian. The method used in this study is the ARIMA model. The results of this study are the ARMA (1.1.0) model suitable for testing inflation volatility in Indonesia. Forecasting results show that inflation over the next 5 months or until December 2022 tends to decrease. From the prediction results, the policy that can be applied to business sector actors is to carry out operational (marketing) activities carried out with an online system. The next policy that can be applied to companies is tax relaxation and easy access to credit to banks. Finally, the policies that can be applied due to the decline in commodity prices in the food and beverage and tobacco sectors are capital assistance and production equipment assistance for business actors.Keywords: Volatility, Inflation, ARIMA, COVID19, Forecasting